2021
DOI: 10.1016/j.jsps.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Topical nitroglycerin in newborns with ischemic injuries: A systematic review

Abstract: Background Arterial catheterization is frequently performed in neonatal intensive care units with an inherent risk of peripheral ischemic injury, especially in preterm infants. The treatment options following vascular damage involve invasive and non-invasive modalities. The primary objective of this systematic review was to evaluate the evidence of the use of topical nitroglycerine (TNG) either alone or as adjunctive therapy. The secondary aim was to develop an approach to the treatment of cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…The proposed mechanism of action for nitroglycerin in this setting is venodilation of patent vessels draining the NAC, which alleviates venous congestion and allows for greater tissue oxygenation. Additionally, arterial vasodilation of patent vessels supplying the NAC compensates for decreased blood flow from superficial vessels that may have been damaged intraoperatively or due to postoperative inflammation [ 2 ]. Topical nitroglycerin is rapidly acting, requiring only 5–10 min for full transdermal absorption, making it an ideal choice in acute care settings [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism of action for nitroglycerin in this setting is venodilation of patent vessels draining the NAC, which alleviates venous congestion and allows for greater tissue oxygenation. Additionally, arterial vasodilation of patent vessels supplying the NAC compensates for decreased blood flow from superficial vessels that may have been damaged intraoperatively or due to postoperative inflammation [ 2 ]. Topical nitroglycerin is rapidly acting, requiring only 5–10 min for full transdermal absorption, making it an ideal choice in acute care settings [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of lidocaine’s effect on vasospasm is contradictory and may therefore not be used in lamb experiments [ 37 ]. In addition, nitroglycerine was discussed as vasodilator, but this has not been mentioned in lamb experiments [ 38 , 39 ] and little experience was present within the experts [F1].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, any infant or child who receives topical NTG should be monitored with blood gas analysis including methaemoglobin levels, oxygenation status and hypotension. In that context, it is reassuring to note that recent systematic reviews that included >25 case reports and a few retrospective studies in newborn infants found topical NTG to be safe and effective in relieving arterial spasm and local ischaemia after peripheral arterial cannulation 19 20…”
Section: Discussionmentioning
confidence: 99%